Utilizing normative theories to develop ethical actions for better privacy practices. Issue 4 (2nd October 2017) - Mohammed, Zareef A.; Tejay, Gurvirender P.; Squillace, Joseph
ABSTRACT: This study examines the privacy practices of organizations. We argue that successful deployment of privacy practices based on ethical actions will strengthen privacy protection measures to better protect clients' PII. We propose a set of ethical actions based on six normative theories following multiple case study approach to study three prominent data breaches. Our analysis indicates that ethical actions based on normative theories can be effective in developing better privacy practices for organizations. The theory that has the strongest effect on privacy practices is the deontological approach, while the liberal-intuitive has the weakest effect on privacy practices.